Pengaruh Brand Image, Brand Love, Brand Equity, Dan Price Terhadap Keputusan Pembelian Produk Sweater Merek Erigo (Studi Kasus pada Mahasiswa FEB Universitas Islam Malang) - Auva Mufaddol; Muhammad Ridwan Basalamah; Arini Fitria Mustapita (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The emergence of modernity has made the fashion sector, experience rapid development, as well as the business competition that is getting tougher every day. Therefore, companies must be able to compete and find ways to win market share for their products. One brand that offers up-to-date fashion trends is the Erigo. Erigo is the most brand in demand and sought after by the public during COVID-19, it has several types of products, such as sweaters, etc. The purpose of the research with this type of explanatory research and quantitative approach is to find out and analyze the effect of brand image, brand love, brand equity, and price on purchasing decisions for Erigo brand sweater products. The Malhotra formula was used to sampling technique for students from the FEB UNISMA, yielding a sample of 100 respondents. This research method uses multiple linear regression analysis with the SPSS analysis tool. This study shows that brand image, brand love, brand equity, and price have a simultaneous effect on purchasing decisions in the test carried out with the partial test, two independent variables have a negative and insignificant effect on the dependent variable, both of which are the brand image and brand love variables. Keywords: Fashion; Brand Image; Brand Love; Brand Equity; Price; Purchasing Decision